دور جودة الخدمات الالكترونية في دعم الاداء المصرفي: دراسة استطلاعية لآراء عينة من العاملين في مصرف بغداد الاهلي (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:             The research aims to determine the relationship between the quality of electronic services and how to properly apply and invest them within banks, and what is its effective role in improving and supporting banking performance, as the National Bank of Baghdad was chosen as a field for research.The researchers highlighted the quality of electronic services as an independent variable and adopted the banking performance variable as a dependent variable, as the research problem was to analyze and explain what is the role of the quality of electronic services in enhancing and supporting banking performance among individuals working in the field under study?The researchers relied on a set of statistical methods and used the Statistical Packages for the Social Sciences (SPSS) program to obtain answers to these questions, in addition to preparing a questionnaire that was distributed to the individuals in the study sample, with a total of (60) respondents. The study reached a set of results, the most important of which is that there is a correlation Between the quality of electronic services and banking performance, this means that the quality of electronic services supports banking performance by improving banking service within the institution under investigation. In light of those conclusions, the researchers presented a set of recommendations, the most important of which is the necessity of improving the information system to improve banking performance and raise the efficiency of banking operations. With the help of the information system , accurate and immediate quality information can be obtained about the bank’s operations and vital financial information, and this would allow the bank’s management to make the most appropriate and effective decisions and better control the bank’s risks.